5. HIGH-SENSITIVITY TROPONIN I IN TYPE 2 DIABETES MELLITUS: ASSOCIATIONS WITH BLOOD PRESSURE, ANEMIA AND RENAL FUNCTION (Vietnam Journal of Community Medicine, 2025)
Objective: Analysis of the relationship between high-sensitivity Troponin I and some cardiovascular risk factors such as hypertension, anemia and renal dysfunction.Methods: A case-control study was conducted on 372 hospitalized patients, divided into type 2 diabetes and non- type 2 diabetes groups.Results: Results showed that high-sensitivity Troponin I levels were significantly higher in type 2 diabetes patients compared to non-diabetics (254.1 ± 745.7 and 95.9 ± 384.8 pg/mL, p < 0.001). High-sensitivity Troponin I was also elevated in patients with anemia and hypertension. A weak but statistically significant inverse correlation was found between hemoglobin and high-sensitivity Troponin I levels (r = -0.1, p = 0.05).Conclusions: High-sensitivity Troponin I tends to be elevated in type 2 diabetes patients with concomitant hypertension, anemia, and renal dysfunction, although the degree of association varies among factors. The increase in high-sensitivity Troponin I in type 2 diabetes patients even in the absence of obvious clinical symptoms suggests a potential role for high-sensitivity Troponin I in assessing early cardiovascular damage in diabetic patients.
Keywords: High-sensitivity Troponin I, type 2 diabetes, hypertension, anemia, renal function.